The impact of social virtual presence agents and content-based product recommendation system on on-line customer purchase intention - Sousa, Francisco Pedroso de (2021)
The appearance of the digital market came as turning point factor, obligating companies to maintain the relationship with consumers by improving and keeping a high technological innovativeness on-line overall experience. The lack of studies on antropomorphization of virtual voice assistances chatbot and the possibilities, yet to be found, on customized product recommendation system variation integration, brought the author to this study. The aim of this research is to investigate the effects of using two different chatbot social virtual presences interactions: with a fully pre-recorded computed personification agent versus with a pre-recorded human social virtual agent; and also understand how having a customized content-based product recommendation system can influence the consumers purchase intention at on-line shopping framework. An on-line platform was developed, recreating a possible virtual store interaction, and the core data was treated using a PLS-SEM model. The results indicate that Human Social Virtual Presence Agent, while assisting the shoppers, have a larger model positive effect on Intellectual stimulus and Hedonic Benefits than a computed personification Agent. This might be explained by the fact that computed imagery and sound Agent was perceived with some amount of emotional creepiness by the participants. Also, recommendation system presence is impacting customers purchase intention on a positive way when compared with not using recommendation system. Thus, this study shows how relevant social interactions are for the customers, especially when done by a human, and how recommendation system has an impact on customers purchase intention.